STATUS HARA DIHUTAN GEWANG (Corypha utan Lamk.), DESA USAPISONBAI, KUPANG, NUSATENGGARA TIMUR - Alhamd, Laode; Partomihardjo, T; Naiola, BP (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Gewang or Corypha utan Lamk. is tree that support the daily need in Usapisonbai village, Nekamese District, Kupang, Nusa Tenggara Timur The nutrient content of the tree is important to be observed, since the tree is crucial to be sustainable.Three permanent plots were established and random sampling was conducted. The results showed that characteristics of soil are clay in texture, somewhat alkaline, mid in C/N ratio, and high CEC (cation exchange capacity) for calcium, magnesium dan potassium.Nutrient contents of soil were 0.15, 0.002, 0.04, 1.16 and 0.04%, respectively, for N, P, K, Ca and Mg. Litter contribution was dominated by leaves (7.73 t ha-), and other parts reached 6.7 t ha , with their nutrient content of N (0.72), P (0.09), K (0.18),Ca (2.S4) and Mg (0.27%). The significant, differences of nitrogen between nutrient contents and between total nutrient contents through litters (P < 0.05) were found. The nutrient contents of tree are 0.57 N, 0.4, P, 0.75 K, 0.77 Ca and 0.18% Mg. The increase of the tree nutrient could be done by utilizing organic matter or by planting tree species that can increase soil fertility and survive in savanna.